2000
DOI: 10.1067/mhn.2000.104807
|View full text |Cite
|
Sign up to set email alerts
|

2[18F]‐Fluoro‐2‐Deoxy‐D‐Glucose Positron Emission Tomography is a Sensitive Tool for the Detection of Occult Primary Cancer (Carcinoma of Unknown Primary Syndrome) with Head and Neck Lymph Node Manifestation

Abstract: 18-FDG-PET should be performed in all patients with CUP syndrome after conventional diagnostic workup fails to identify the primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
13

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(76 citation statements)
references
References 25 publications
5
58
0
13
Order By: Relevance
“…Others have shown the benefit of PET in the detection of unknown primary head and neck cancers or synchronous primary tumours [77,78]. One advantage of PET over other imaging modalities, such as computed tomography (CT) or magnetic resonance imaging (MRI), is that since PET imaging visualizes metabolic processes in vivo, relatively small tumours can be detected before structural changes have taken place, as long as they are metabolically active [79].…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Others have shown the benefit of PET in the detection of unknown primary head and neck cancers or synchronous primary tumours [77,78]. One advantage of PET over other imaging modalities, such as computed tomography (CT) or magnetic resonance imaging (MRI), is that since PET imaging visualizes metabolic processes in vivo, relatively small tumours can be detected before structural changes have taken place, as long as they are metabolically active [79].…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…larynx, and upper esophagus), anatomic imaging with CT and/or MRI, and blind tongue base biopsy. Numerous studies have addressed the ability of PET to identify primary locations after traditional work-up [29][30][31]. A meta-analysis by Rusthoven and colleagues [32] showed that PET was able to recognize a primary tumor after negative conventional work-up in one quarter of patients with an overall sensitivity and specificity of 88% and 75%, respectively.…”
Section: Unknown Primary Tumorsmentioning
confidence: 99%
“…7,[9][10][11][12][13][14][15][16][17][18][19][20] These figures, however, were reported in series that included patients with CUP and extracervical metastases as well as varying cancer types, for example, SCC, adenocarcinoma, melanoma, large cell carcinoma, plasmocytoma, etc., and the diagnostic performance of FDG-PET was not determined separately for cervical versus extracervical CUP presentations and as a function of the histological subtype. Further, in several of these studies, the PET methodology was either not standardized or inadequate and most of these studies were conducted using FDG-PET and not FDG-PET/CT, which might have resulted in a higher rate of false-positive findings and sensitivity.…”
mentioning
confidence: 99%